Testing the fading affect bias for healthy coping in the context of death. Issue 8 (13th September 2016) - Gibbons, Jeffrey A.; Fehr, Ashley M. A.; Brantley, J. Claire; Wilson, Kalli J.; Lee, Sherman A.; Walker, W. Richard
ABSTRACT: Affect fades faster for unpleasant events than for pleasant events (e.g., Walker, Vogl, & Thompson, 1997 ), which is referred to as the fading affect bias (FAB; Walker, Skowronski, Gibbons, Vogl, & Thompson, 2003 ). Although research has generally shown that the FAB is a healthy coping mechanism, this same finding has not been demonstrated at a specific level of analysis accounting for particular event types and related individual differences (e.g., Gibbons et al., 2013 ). Given the strong unpleasant emotions associated with death (Rask, Kaunonen, & Paunonen-Ilmonen, 2002 ), the current study examined FAB in the context of death events and participant attitudes toward death. General healthy coping was shown by robust FAB across death and control (i.e., everyday) events and by a negative correlation between negative religious coping and FAB. Although healthy coping at a specific level of analysis was supported by increased FAB for participants who held accepting attitudes toward death when they recalled everyday events, it was not supported by decreased FAB for the same participants when they recalled death events. This effect was mediated by rehearsal ratings, not depression. Implications are discussed.